Psychology and Lifestyle Related to Coronary Heart Desease Incidence - Harwiyandi Ningsih; Ancah Caesarina Novi Marchianti; Isa Ma’rufi (Health Notions, 2018)
Coronary heart disease is a disease of the coronary arteries that narrows or blocks the coronary arteries caused by the process of atherosclerosis. A preliminary study conducted by researchers in outpatients at the PTPN X Hospital of Jember showed that the prevalence of coronary heart disease was quite high, as evidenced by the medical record data that new outpatient coronary heart disease from year to year showed a fluctuating pattern. In 2015 it amounted to 22.6%, in 2016 amounted to 15.95% and in 2017 it increased dramatically by 29.07%, sufferers consumed foods that were high in fat, then consumed excessive coffee, smoked at a young age and some sufferers experiencing stress due to competition in the world of work. The purpose of this study was to determine the psychology and lifestyle relationship to coronary heart disease in outpatients at the PTPN X Hospital of Jember. This research was quantitative with analytic observational method with case control design. The sample was 57 in outpatients at PTPN X Hospital of Jember who were taken by systematic random sampling. Logistics regression was used to analyze data. The results there were relationship of stress (p-value: 0.003), depression (p-value: 0.006) and physical activity (p-value: 0.009) to coronary heart disease. Keywords: Psychology, Lifstyle, Coronary heart disease